Protective Effect of Daidzein on Ifosfamide-Induced Neurotoxicity Via Improving Some Selected Oxidative Stress Parameters in Male Rats - Zaki Hammodi, Hiba; Naji Al-Shawi, Nada (Iraqi Journal of Pharmaceutical Sciences, 2023)
In this study, the possible protective effects of daidzein on ifosfamide-induced neurotoxicity in male rats were examined by the determination of changes in selected oxidant–antioxidant markers of male rats’ brain tissue.Twenty-eight (28) apparently-healthy Wistar male rats weighing (120-150gm) allocated into 4 groups (n=7) were used in this study. Rats orally-administered 1% tween 20 dissolved in distilled water/Control (Group I); rats were orally-administered daidzein suspension (100mg/kg) for 7 days (Group II); rats intraperitoneally-injected with a single dose of ifosfamide (500 mg/kg) (Group III); rats orally-administered for 7 days with the daidzein (100mg/kg) before a single intraperitoneal dose of ifosfamide (500 mg/kg) at day 7 (Group IV). Twenty-four (24) hours after the end of treatment, determination of the malondialdehyde, reduced glutathione, and superoxide dismutase enzyme activity levels in the rats’ brain tissue homogenate were performed; in addition to the histopathological examination of the brain tissues sections. Results showed that the levels of malondialdehyde in brain tissue were significantly-increased (P<0.05) in (Group III/ifosfamide-only) rats compared to such level in the rats’ brain tissue of controls (Group I). Furthermore, the brain tissue level of the malondialdehyde was significantly-decreased (P<0.05) in rats of Group IV (orally-administered DZN prior to IFO) compared to such tissue level in rats of Group III. Moreover, the brain levels of each of the reduced glutathione and the superoxide dismutase enzyme activity were significantly-decreased (P<0.05) in (Group III) compared to each level in those of Group I. Additionally, the brain levels of each of the antioxidant parameters was significantly-increase (P<0.05) in Group IV rats compared to each of these tissue levels in rats of Group III.As a results, daidzein has a protective effect against ifosfamide-induced neurotoxicity in rats via improving some selected oxidative stress parameters in male rats.